Influence of Swirl Number on Semi-Confined Flames - M. Teresa Parra-Santos; Ruben Perez; Victor Mendoza; Miguel A. Rodriguez; Francisco Castro (International Journal of Applied Methods in Electronics and Computers, 2016)
Stoichiometric methane air swirling flame has been modelled using RANS equations and a simplified mechanisms of reaction. The reaction zone is strongly affected by the swirl intensity. The higher the swirl number is, the narrower the reaction zone is. The thermodynamic state of reaction products matches well that of equilibrium state at constant pressure.